Hard carbon negative electrode material and preparation method and application thereof
Through the acid-eluting ash and fluidized bed pre-oxidation process, the particle size distribution and oxidation uniformity of the hard carbon negative electrode material are optimized, and the problems of impurities, uneven oxidation, high energy consumption and unsatisfactory particle size distribution in the preparation process in the prior art are solved, thereby achieving efficient preparation of high-quality hard carbon materials.
Patent Information
- Application Number
- CN202510083193.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-20
AI Technical Summary
In the prior art, there are problems such as many impurity components, uneven preoxidation, high energy consumption and unsatisfactory particle size distribution during the preparation of hard carbon negative electrode materials, which affect the consistency of material performance and electrochemical performance.
The pickling-eluting ash and fluidized bed preoxidation process is adopted, and the pickling and fluidized bed oxidation treatment are performed by mixing hard carbon precursors of different particle sizes. Combined with the high-temperature carbonization step, the particle size distribution and oxidation uniformity of the material are optimized.
It significantly shortens the preparation cycle, reduces energy consumption, improves the specific capacity and cycle stability of hard carbon materials, enhances the consistency of electrochemical performance, and is suitable for high-rate charging and discharging applications.
Smart Images

Figure CN119841304A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials and relates to a hard carbon negative electrode material and a preparation method and application thereof. Background Art
[0002] At present, lithium-ion batteries are widely used in mobile electronic devices, new energy vehicles, power tools and other fields due to their high energy density and excellent safety performance. However, the limited and expensive lithium resources limit the application of lithium-ion batteries in large-scale energy storage systems. Compared with lithium, sodium resources are abundant in the earth's crust and are cheap, so sodium-ion batteries have broad application prospects in large-scale energy storage systems.
[0003] The radius of sodium ions is larger than that of lithium ions, and it is difficult to embed them into the interlayer spacing of graphite negative electrodes. Therefore, graphite negative electrodes are not suitable as negative electrode materials for sodium ion batteries. The amorphous hard carbon has a disordered and curved carbon layer, which can store sodium in a variety of ways such as intercalation, adsorption and pore filling. It has a higher capacity. Therefore, hard carbon has great practical application prospects as a negative electrode material for sodium ion batteries.
[0004] Unlike hard carbon, soft carbon materials prepared from coal tar pitch / petroleum pitch / coal / heavy carbon, etc. have good conductivity, but the carbon layer has a high degree of order and a small interplanar spacing, and the electrochemical performance is poor when directly applied to the negative electrode of a sodium ion battery. The commonly used modification method is to pre-oxidize the precursor to obtain a cross-linked structure, thereby increasing the disorder of the carbon layer and the interplanar spacing, and further improving the sodium storage performance. However, it is difficult to enhance the pre-oxidation effect of the precursor using conventional static pre-oxidation methods (muffle furnace, tubular furnace, fixed bed) for precursors with different physical and chemical properties. The entire process is greatly affected by impurities on the precursor particles, the diversity of particle distribution and the limitations of the oxidation method, resulting in insufficient or excessive oxidation reaction, unsatisfactory particle size distribution, long process cycle and high energy consumption, which increases the difficulty of obtaining an ideal cross-linked structure and thus forming a hard carbon material with high sodium storage capacity and excellent rate.
[0005] CN115188952A discloses a method for air oxidation modification of asphalt using a kneading pot. The process of preparing hard carbon materials is optimized through molecular distillation, oxidation treatment, crushing, air stabilization and high-temperature carbonization, and finally a negative electrode material with excellent electrochemical properties is formed. However, the patent does not solve the problem of oxidation uniformity, which may affect the consistency of material performance; the impurities in coal tar are not deeply treated, which may affect the conductivity and cycle performance of the hard carbon; the particle size control accuracy is limited, which may bring challenges to the consistency of electrode production.
[0006] CN107986254A proposes a method for preparing hard carbon negative electrode materials through kneading, carbonization and high-temperature carbonization steps. This method uses aggregates and asphalt to mix, increases the surface oxygen-containing functional groups through oxidation modification, and then undergoes a two-step carbonization process to prepare hard carbon materials with high lithium storage pores and reasonable particle size distribution. However, the patent's oxidation modification requires strict control of air flow rate and kneading uniformity, and the operation is complicated; no impurity removal process is mentioned, which may affect the purity of the material; the method is highly dependent on high-temperature equipment, which may increase the cost of industrialization.
[0007] CN118454887A proposes a deep deashing and dechlorination process and system for high-chlorine coal, which adopts pre-screening, jig separation, liquid-solid fluidized bed and flotation technologies to achieve efficient removal of chlorine and ash in coal, and combines improved H2O2 oxidation and ultrasonic treatment technology to further remove the sulfur content in coal and improve the quality of clean coal. However, the process flow is complicated and highly dependent on jigs, multi-stage equipment and ultrasonic equipment; the preparation of iron-doped carbon dots is relatively cumbersome and may increase costs; the industrial adaptability and economy of some processing steps need to be further verified. Summary of the invention
[0008] The purpose of the present invention is to provide a hard carbon negative electrode material and a preparation method and application thereof. The present invention solves the problems of multiple impurity components in the negative electrode material, uneven pre-oxidation, high energy consumption and unsatisfactory particle size distribution, improves the fluidization state and pre-oxidation effect of ultrafine viscous particles in the fluidized bed, realizes the efficient preparation of high-quality hard carbon materials, and provides better quality negative electrode materials for power batteries and energy storage systems.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing a hard carbon negative electrode material, the preparation method comprising the following steps:
[0011] (1) performing pickling and deashing treatment on a first particle size hard carbon precursor and a second particle size hard carbon precursor to obtain a first particle size pickled precursor and a second particle size pickled precursor, and mixing the first particle size pickled precursor and the second particle size pickled precursor to obtain a mixed pickled precursor;
[0012] (2) subjecting the mixed acid-washed precursor to fluidized bed oxidation treatment and then screening to obtain an oxidized material with a first particle size and an oxidized material with a second particle size;
[0013] (3) sintering the first particle size oxide material to obtain the hard carbon negative electrode material;
[0014] Among them, the median particle size D50 of the first particle size pickling precursor is ≤ 30 μm, the median particle size D50 of the second particle size pickling precursor is > 30 μm, the median particle size D50 of the first particle size oxidized material is ≤ 30 μm, and the median particle size D50 of the second particle size oxidized material is > 30 μm.
[0015] For the first particle size hard carbon precursor and the second particle size hard carbon precursor of the present invention, they can be mixed first and then pickled, or pickled separately and then mixed. There is no clear limitation here.
[0016] The present invention prepares high-quality hard carbon materials by introducing pickling and deashing, the pre-oxidation process of matching fine and coarse particles in a fluidized bed, and precise particle size control technology. By adopting the pre-oxidation process of matching fine and coarse particles in a fluidized bed, the precursor particles can uniformly contact the oxidant in the fluidized environment, thereby significantly improving the oxidation uniformity and ensuring the stability of product performance.
[0017] Preferably, the median particle size 2 μm ≤ D50 ≤ 30 μm of the first particle size hard carbon precursor, for example: 2 μm, 5 μm, 10 μm, 20 μm, or 30 μm, etc. It is not limited to the listed values, and other unlisted values within this numerical range are equally applicable. The median particle size 30 μm < D50 ≤ 200 μm of the second particle size hard carbon precursor, for example: 35 μm, 50 μm, 100 μm, 150 μm, or 200 μm, etc. It is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.
[0018] The median particle size 2 μm ≤ D50 ≤ 30 μm of the first particle size pickling precursor, for example: 2 μm, 5 μm, 10 μm, 20 μm, or 30 μm, etc. It is not limited to the listed values, and other unlisted values within this numerical range are equally applicable. The median particle size 30 μm < D50 ≤ 200 μm of the second particle size pickling precursor, for example: 35 μm, 50 μm, 100 μm, 150 μm, or 200 μm, etc. It is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.
[0019] The median particle size 2 μm ≤ D50 ≤ 30 μm of the first particle size oxidized material, for example: 2 μm, 5 μm, 10 μm, 20 μm, or 30 μm, etc. It is not limited to the listed values, and other unlisted values within this numerical range are equally applicable. The median particle size 30 μm < D50 ≤ 200 μm of the second particle size oxidized material, for example: 35 μm, 50 μm, 100 μm, 150 μm, or 200 μm, etc. It is not limited to the listed values, and other unlisted values within this numerical range are equally applicable.
[0020] Preferably, in step (2), the second particle size oxide material is crushed and sieved to obtain an oxide material with a median particle size of 2μm≤D50≤30μm, and then mixed with a new second particle size acid-washed precursor, and the fluidized bed oxidation treatment and screening steps of step (2) are repeated.
[0021] The present invention supplements larger-sized raw materials (new second-particle-size acid-washed precursors) as fluidized bed materials, reasonably improves particle flowability, reduces the risk of agglomeration of ultrafine sticky particles of small-sized raw materials (crushed second-particle-size oxidized materials), and repeats this cycle, which can significantly improve the heat transfer and mass transfer effects in the fluidized bed. The present invention screens the raw materials and performs secondary crushing (less than 30 μm) and secondary oxidation of coarse particles, and controls the particle size before and after fluidized bed oxidation, respectively, to ensure that the particle size distribution of the material meets the requirements of electrode preparation, and improve the conductivity and cycle stability of the battery.
[0022] Preferably, in step (1), the first particle size hard carbon precursor and the second particle size hard carbon precursor are obtained by crushing, grinding, screening and drying the precursor carbon material.
[0023] The first particle size hard carbon precursor and the second particle size hard carbon precursor of the present invention can be obtained by crushing, grinding, screening and drying the same batch of precursor materials, or by crushing, grinding, screening and drying the precursor materials of different batches.
[0024] Preferably, the precursor carbon material includes any one of coal tar pitch, petroleum pitch, coal, biomass carbon material or heavy carbon material, or a combination of at least two of them. Typical but non-limiting combinations include a combination of coal tar pitch and petroleum pitch, a combination of coal and biomass carbon material, or a combination of petroleum pitch and coal, etc.
[0025] Preferably, the drying temperature is 100°C to 110°C, for example, 100°C, 102°C, 105°C, 108°C or 110°C, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Preferably, the pickling and deashing treatment in step (1) includes hydrochloric acid pickling and hydrofluoric acid pickling.
[0027] Preferably, the mass concentration of the hydrochloric acid used in the hydrochloric acid washing is 15% to 20%, for example: 15%, 16%, 17%, 18%, 19% or 20%, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the solid-liquid mass volume ratio of the hydrochloric acid washing is 1: (5-15) g / mL, for example: 1: 5 g / mL, 1: 8 g / mL, 1: 10 g / mL, 1: 12 g / mL or 1: 15 g / mL, etc., not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0029] Preferably, stirring is performed during the hydrochloric acid washing process.
[0030] Preferably, the stirring speed is 50 rpm to 150 rpm, for example, 50 rpm, 80 rpm, 100 rpm, 120 rpm or 150 rpm, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] Preferably, the stirring time is 10 h to 15 h, for example, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0032] Preferably, the hydrochloric acid washing is followed by standing and water washing, silver nitrate is added to the water washing solution, and drying is performed after no white precipitate is generated.
[0033] Preferably, the standing time is 1 h to 3 h, for example, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] Preferably, the temperature of the drying treatment is 100°C to 110°C, for example, 100°C, 102°C, 105°C, 108°C or 110°C, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the drying treatment time is 10 h to 15 h, for example, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the mass concentration of the hydrofluoric acid used in the hydrofluoric acid washing is 35% to 45%, for example, 35%, 38%, 40%, 42% or 45%, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the solid-liquid mass volume ratio of the hydrofluoric acid washing is 1:(5-10) g / mL, for example: 1:5 g / mL, 1:6 g / mL, 1:8 g / mL, 1:9 g / mL or 1:10 g / mL, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, stirring is performed during the hydrofluoric acid washing process.
[0039] Preferably, the stirring speed is 50 rpm to 150 rpm, for example, 50 rpm, 80 rpm, 100 rpm, 120 rpm or 150 rpm.
[0040] Preferably, the stirring time is 20 h to 30 h, for example, 20 h, 22 h, 25 h, 28 h or 30 h, etc., and is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0041] Preferably, the hydrofluoric acid washing is followed by standing and water washing, calcium chloride is added to the water washing solution, and drying is performed after no white precipitate is generated.
[0042] Preferably, the standing time is 2 h to 4 h, for example, 2 h, 2.5 h, 3 h, 3.5 h or 4 h.
[0043] Preferably, the temperature of the drying treatment is 100°C to 110°C, for example, 100°C, 102°C, 105°C, 108°C or 110°C, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] Preferably, the drying treatment time is 10 h to 15 h, for example, 10 h, 11 h, 12 h, 13 h, 14 h or 15 h, etc., and is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In the mixed pickling precursor described in step (2), the mass ratio of the first particle size pickling precursor to the second particle size pickling precursor is 1:(2-5), for example: 1:2, 1:2.5, 1:3, 1:4 or 1:5, etc., not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0046] Preferably, the atmosphere of the fluidized bed oxidation treatment in step (2) comprises an oxygen-containing gas.
[0047] Preferably, the gas flow rate of the fluidized bed oxidation treatment in step (2) is 700 mL / min to 800 mL / min, for example, 700 mL / min, 720 mL / min, 750 mL / min, 780 mL / min or 800 mL / min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] Preferably, the heating rate of the fluidized bed oxidation treatment in step (2) is 0.4°C / min to 1°C / min, for example: 0.4°C / min, 0.5°C / min, 0.6°C / min, 0.8°C / min, 0.9°C / min or 1°C / min, etc.
[0049] Preferably, the temperature of the fluidized bed oxidation treatment in step (2) is 200°C to 350°C, for example, 200°C, 220°C, 250°C, 300°C or 350°C.
[0050] Preferably, the fluidized bed oxidation treatment in step (2) includes a first stage of fluidized bed oxidation treatment and a second stage of fluidized bed oxidation treatment.
[0051] Preferably, the temperature of the first stage fluidized bed oxidation treatment is 200°C to 300°C, for example, 220°C, 230°C, 240°C, 260°C or 280°C, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, the time of the first stage fluidized bed oxidation treatment is 2h to 6h, for example: 2h, 3h, 4h, 5h or 6h, etc., not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0053] Preferably, the temperature of the second stage fluidized bed oxidation treatment is 300°C to 350°C, for example, 300°C, 310°C, 320°C, 340°C or 350°C, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] Preferably, the time of the second stage fluidized bed oxidation treatment is 3 h to 5 h, for example: 3 h, 3.5 h, 4 h, 4.5 h or 5 h.
[0055] Preferably, the atmosphere of the sintering treatment in step (3) includes an inert gas.
[0056] Preferably, the temperature of the sintering treatment in step (3) is 1200°C to 1500°C, for example, 1200°C, 1250°C, 1300°C, 1400°C or 1500°C, etc., not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] Preferably, the sintering time in step (3) is 3 h to 8 h, for example, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h, etc., and is not limited to the listed values. Other values not listed within the range are also applicable.
[0058] Preferably, the sintering treatment in step (3) is followed by an airflow classification and shaping treatment.
[0059] Preferably, after the airflow classification and shaping treatment, the median particle size D50 of the hard carbon negative electrode material obtained is 2μm to 10μm, for example: 2μm, 3μm, 5μm, 8μm or 10μm, etc., not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0060] In a second aspect, the present invention provides a hard carbon negative electrode material, which is prepared by the preparation method described in the first aspect.
[0061] In a third aspect, the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the hard carbon negative electrode material as described in the second aspect.
[0062] In a fourth aspect, the present invention provides a battery, comprising the negative electrode plate as described in the third aspect.
[0063] Compared with the prior art, the present invention has the following beneficial effects:
[0064] (1) The present invention adopts acid washing and deashing and fluidized bed pre-oxidation process, which greatly shortens the preparation cycle and reduces energy consumption. Compared with the traditional static oxidation method, the production efficiency is increased by more than 100%, and the consistency of the performance of hard carbon materials is improved.
[0065] (2) The present invention achieves a high specific capacity and cycle stability through the coordinated optimization of oxidation, screening and high-temperature carbonization, and is particularly suitable for high-rate charge and discharge applications.
[0066] (3) The present invention adopts precise screening and acid washing and deashing processes in the precursor treatment stage, which significantly reduces the impact of inorganic impurities on material properties, reduces energy consumption and by-product generation in the subsequent carbonization stage, and is environmentally friendly and economical. At the same time, the initial pre-oxidation of larger particles and the secondary pre-oxidation after crushing reduce the difficulty of pre-oxidation of larger particles during the pre-oxidation process, greatly reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 It is a process flow chart of preparing the hard carbon negative electrode material provided by an embodiment of the present invention, wherein the first particle size particles are small particle size particles, and the second particle size particles are large particle size particles. DETAILED DESCRIPTION
[0068] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0069] Example 1
[0070] This embodiment provides a hard carbon negative electrode material. The preparation process flow chart of the hard carbon negative electrode material is as follows: Figure 1 As shown, the preparation method of the hard carbon negative electrode material comprises the following steps:
[0071] (1) First, crush coal tar pitch using a jaw crusher (5E-JCA), pre-dry it at 105 °C in a forced-air drying oven, then grind it using a pulverizer (5E-PCIX100), sieve it using a standard sieve shaker, and select the first particle size hard carbon precursor with a median particle size D50 of 2 μm to 30 μm and the second particle size hard carbon precursor with a median particle size D50 of 50 μm to 200 μm. Dry them at 105 °C for 4 h. Mix the first particle size hard carbon precursor and the second particle size hard carbon precursor with 18% mass fraction of HCl at a ratio of 1:10 g / mL respectively, stir and wash the coal for 12 h at a speed of 100 rpm, let it stand for 2 h, and wash it repeatedly with distilled water until there is no Cl - (Checked using AgNO3, no white precipitate) Filter, dry it in a forced-air drying oven at 105 °C for 12 h to obtain the demineralized raw material. Weigh the demineralized raw material and mix it with 40% mass concentration of hydrofluoric acid at a ratio of 1:7.5 g / mL, stir at a speed of 100 rpm for 24 h, let it stand for 3 h, filter, and wash the filter cake with distilled water and wash it multiple times (the filter cake needs to be stirred and mixed with distilled water in a beaker and filtered) until there is no F - (Checked using CaCl2), then dry it at 105 °C for 12 h to obtain the first particle size pickled precursor and the second particle size pickled precursor. Mix the first particle size pickled precursor and the second particle size pickled precursor according to a mass ratio of 1:3 to obtain the mixed pickled precursor;
[0072] (2) Place the mixed pickled precursor in a fluidized bed. In an air atmosphere, select an air velocity of 740 mL / min; at a heating rate of 0.5 °C / min, heat from room temperature to 260 °C, carry out the first-stage fluidized bed pre-oxidation treatment for 4 h, and then heat to 330 °C at the same heating rate to carry out the second-stage fluidized bed pre-oxidation treatment for 4 h. Screen the materials after the fluidized bed pre-oxidation. Collect the particles with a median particle size of 2 μm ≤ D50 ≤ 30 μm (the first particle size oxidized material) as the materials for high-temperature carbonization; crush the particles with a median particle size of 30 μm < D50 ≤ 200 μm (the second particle size oxidized material) to particles with a median particle size of 2 μm ≤ D50 ≤ 30 μm as the materials for the next fluidized bed pre-oxidation to obtain the first particle size pickled precursor, mix it with the new second particle size pickled precursor, and repeat the fluidized bed oxidation treatment and screening steps in step (2). Repeat the fluidized bed pre-oxidation and crushing and screening steps N times;
[0073] (3) Place the first particle size oxidized material in the constant temperature zone of a tube furnace, heat it to 1400 °C at a heating rate of 1 °C / min in an argon atmosphere and keep it at a constant temperature for 5 h. After airflow classification and shaping treatment, obtain the hard carbon negative electrode carbon material with a median particle size D50 of 2 μm to 10 μm.
[0074] Example 2
[0075] This embodiment provides a hard carbon negative electrode material. The preparation process flow chart of the hard carbon negative electrode material is as follows: Figure 1 As shown, the preparation method of the hard carbon negative electrode material comprises the following steps:
[0076] (1) First, the heavy carbon (liquefied residue) was crushed by a jaw crusher (5E-JCA), pre-dried in a blast drying oven at 105°C, then ground by a pulverizer (5E-PCIX100), sieved by a standard sieve vibrating screen, and the first particle size hard carbon precursor with a median particle size D50 of 2μm to 5μm and the second particle size hard carbon precursor with a median particle size D50 of 40μm to 200μm were selected and dried at 105°C for 4h. The first particle size hard carbon precursor and the second particle size hard carbon precursor were respectively mixed with 20% HCl by mass at a ratio of 1:5g / mL, stirred at a speed of 50rpm for 15h, left to stand for 3h, and repeatedly washed with distilled water until there was no Cl - (Use AgNO3 to check, no white precipitate) filter, dry in a blast drying oven at 100°C for 15h to obtain demineralized raw materials, weigh the demineralized raw materials and mix them with 40% hydrofluoric acid at a ratio of 1:10g / mL, stir at 150rpm for 20h, let stand for 4h, filter and wash the filter cake with distilled water, wash several times (stir the filter cake with distilled water in a beaker for several times and filter) until there is no F - (CaCl2 detection), and then dried at 100°C for 15h to obtain a first particle size pickling precursor and a second particle size pickling precursor, and the first particle size pickling precursor and the second particle size pickling precursor were mixed in a mass ratio of 1:2 to obtain a mixed pickling precursor;
[0077] (2) Place the mixed pickling precursor in a fluidized bed in an air atmosphere at a gas velocity of 700 mL / min; heat the mixture from room temperature to 200°C at a heating rate of 0.8°C / min, perform the first stage of fluidized bed pre-oxidation for 6 hours, and then heat the mixture to 320°C at the same heating rate for a second stage of fluidized bed pre-oxidation for 3 hours. Screen the material after fluidized bed pre-oxidation, and collect particles with a median particle size of 2μm≤D50≤5μm (first particle size oxidized material) as the material for high-temperature carbonization; crush particles with a median particle size of 40μm≤D50≤200μm (second particle size oxidized material) to particles with a median particle size of 2μm≤D50≤5μm as the material for the next fluidized bed pre-oxidation to obtain the first particle size pickling precursor, mix it with the new second particle size pickling precursor, and repeat the fluidized bed oxidation and sieving steps of step (2), and repeat the fluidized bed pre-oxidation and crushing and sieving steps N times;
[0078] (3) Placing the first particle size oxide material in the constant temperature zone of a tubular furnace, heating it to 1500°C at a heating rate of 1°C / min under an argon atmosphere and keeping the temperature constant for 3 hours, and obtaining a hard carbon negative electrode carbon material with a median particle size D50 of 2μm to 10μm after airflow classification and shaping.
[0079] Example 3
[0080] This embodiment provides a hard carbon negative electrode material. The preparation process flow chart of the hard carbon negative electrode material is as follows: Figure 1 As shown, the preparation method of the hard carbon negative electrode material comprises the following steps:
[0081] (1) First, the long flame coal was crushed by a jaw crusher (5E-JCA), pre-dried in a blast drying oven at 110°C, then ground by a pulverizer (5E-PCIX100), sieved by a standard sieve vibrating screen, and the first particle size hard carbon precursor with a median particle size D50 of 2μm to 20μm and the second particle size hard carbon precursor with a median particle size D50 of 50μm to 200μm were selected and dried at 110°C for 4h. The first particle size hard carbon precursor and the second particle size hard carbon precursor were respectively mixed with 20% HCl at a ratio of 1:15g / mL, stirred at a speed of 150rpm for 10h, left to stand for 1h, and repeatedly washed with distilled water until there was no Cl - (Use AgNO3 to check, no white precipitate) filter, dry in a blast drying oven at 100°C for 15h to obtain demineralized raw materials, weigh the demineralized raw materials and mix them with 40% hydrofluoric acid at a ratio of 1:5g / mL, stir at 50rpm for 30h, let stand for 4h, filter and wash the filter cake with distilled water, wash several times (stir the filter cake with distilled water in a beaker for several times and filter) until there is no F - (CaCl2 detection), and then dried at 100°C for 15h to obtain a first particle size pickling precursor and a second particle size pickling precursor, and the first particle size pickling precursor and the second particle size pickling precursor were mixed in a mass ratio of 1:5 to obtain a mixed pickling precursor;
[0082] (3) Place the mixed pickling precursor in a fluidized bed in an oxygen atmosphere at a gas velocity of 800 mL / min; heat the mixture from room temperature to 300°C at a heating rate of 1°C / min, perform the first stage of fluidized bed pre-oxidation for 2 hours, and then heat the mixture to 350°C at the same heating rate for a second stage of fluidized bed pre-oxidation for 5 hours. Screen the material after fluidized bed pre-oxidation, and collect particles with a median particle size of 2μm≤D50≤20μm (first particle size oxidized material) as the material for high-temperature carbonization; crush particles with a median particle size of 50μm≤D50≤200μm (second particle size oxidized material) to particles with a median particle size of 2μm≤D50≤20μm as the material for the next fluidized bed pre-oxidation to obtain the first particle size pickling precursor, mix it with the new second particle size pickling precursor, and repeat the fluidized bed oxidation and sieving steps of step (2), and repeat the fluidized bed pre-oxidation and crushing and sieving steps N times;
[0083] (3) Placing the first particle size oxide material in the constant temperature zone of a tubular furnace, heating it to 1200°C at a heating rate of 1°C / min under an argon atmosphere and keeping the temperature constant for 8 hours, and obtaining a hard carbon negative electrode carbon material with a median particle size D50 of 2μm to 10μm after airflow classification and shaping.
[0084] Example 4
[0085] The difference between this embodiment and embodiment 1 is that only one stage of fluidized bed oxidation treatment is performed at a temperature of 330° C., and other conditions and parameters are exactly the same as those in embodiment 1.
[0086] Example 5
[0087] The only difference between this embodiment and Embodiment 1 is that, in the mixed pickling precursor, the mass ratio of the first particle size pickling precursor to the second particle size pickling precursor is 1:1, and the other conditions and parameters are exactly the same as those in Embodiment 1.
[0088] Example 6
[0089] The only difference between this embodiment and Embodiment 1 is that, in the mixed pickling precursor, the mass ratio of the first particle size pickling precursor to the second particle size pickling precursor is 1:6, and the other conditions and parameters are exactly the same as those in Embodiment 1.
[0090] Example 7
[0091] The only difference between this embodiment and embodiment 1 is that the gas flow rate of the fluidized bed oxidation treatment is 600 mL / min, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0092] Example 8
[0093] The only difference between this embodiment and embodiment 1 is that the gas flow rate of the fluidized bed oxidation treatment is 900 mL / min, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0094] Example 9
[0095] The only difference between this embodiment and embodiment 3 is that only one stage of fluidized bed oxidation treatment is performed at a temperature of 300° C., and other conditions and parameters are exactly the same as those in embodiment 3.
[0096] Comparative Example 1
[0097] The only difference between this comparative example and Example 1 is that no acid washing and deashing treatment is performed, and other conditions and parameters are exactly the same as those in Example 1.
[0098] Comparative Example 2
[0099] The only difference between this comparative example and Example 1 is that a single large particle size (50 μm to 200 μm) acid-washing precursor is used, and other conditions and parameters are exactly the same as those in Example 1.
[0100] Comparative Example 3
[0101] The only difference between this comparative example and Example 1 is that a single small particle size (2 μm to 30 μm) acid-washing precursor is used, and other conditions and parameters are exactly the same as those in Example 1.
[0102] Comparative Example 4
[0103] The only difference between this comparative example and Example 1 is that tubular furnace oxidation is used instead of fluidized bed oxidation, and other conditions and parameters are exactly the same as those in Example 1.
[0104] Comparative Example 5
[0105] The only difference between this comparative example and Example 3 is that tubular furnace oxidation is used instead of fluidized bed oxidation, and other conditions and parameters are exactly the same as those in Example 3.
[0106] Performance Test:
[0107] The hard carbon negative electrode material obtained in the embodiment and the comparative example was ground, bonded, and magnetically stirred to prepare the material in a slurry process according to the mass ratio of active material: SP: CMC: SBR = 90:4:2:4. The specific process parameters were: stirring for 27 minutes with a single cup homogenizer, a speed of 1950 rpm, degassing for 3 minutes, and a speed of 2150 rpm.
[0108] The coating process selected a thickness of 100 μm and a surface density of 2.5 mg / cm 2 After drying, the pole piece is rolled and cut directly into pieces and weighed. The battery test selected a static time of 7h. The test environment is temperature: 25±1℃; humidity: 40%RH.
[0109] The above-mentioned electrode was used as the negative electrode, sodium as the positive electrode, the electrolyte was 1 mol / L NaPF6 dissolved in EC:DMC (1:1), and the diaphragm was glass fiber (GF / D), and electrochemical tests were carried out. The test results are shown in Table 1:
[0110] Table 1
[0111]
[0112]
[0113] As can be seen from Table 1, from Examples 1-8, the 0.1C charging specific capacity of the battery made of the hard carbon negative electrode material of the present invention can reach more than 300mAh / g, the 1C charging specific capacity can reach more than 265mAh / g, the 5C charging specific capacity can reach more than 230mAh / g, the first coulombic efficiency can reach more than 88.6%, and the capacity retention rate after 100 cycles can reach more than 83.4%. In the preparation process of the hard carbon negative electrode material of the present invention, the carbonization temperature, oxidizing atmosphere and fluidized bed oxidation conditions significantly affect the micropore structure, specific capacity and cycle performance of the material. Appropriately increasing the carbonization temperature to 1400°C and optimizing the oxidation conditions (such as fluidized bed gas velocity and oxidation stage control) can effectively improve the specific capacity and first coulombic efficiency of hard carbon materials. The 0.1C charging specific capacity can reach more than 310mAh / g, the 1C charging specific capacity can reach more than 275mAh / g, the 5C charging specific capacity can reach more than 240mAh / g, the first coulombic efficiency can reach more than 90.6%, and the capacity retention rate after 100 cycles can reach more than 87.5%.
[0114] By comparing Example 1 with Example 4, it can be seen that in the preparation process of the hard carbon negative electrode carbon material of the present invention, the use of segmented fluidized bed oxidation treatment (such as two-stage temperature control) can significantly improve the oxidation uniformity and the final electrochemical performance of the material. Due to the insufficient oxidation depth, the material performance of the single-stage oxidation treatment is significantly reduced compared with Example 1, which is manifested as a decrease in specific capacity and cycle performance.
[0115] By comparing Example 1 and Examples 5-6, it can be seen that in the preparation process of the hard carbon negative electrode carbon material described in the present invention, the ratio of the first particle size pickled precursor to the second particle size pickled precursor will affect its performance. The mass ratio of the first particle size pickled precursor to the second particle size pickled precursor is controlled at 1: (2-5), and the performance of the hard carbon negative electrode material obtained is better. If the proportion of the first particle size pickled precursor (small particle size) is too high, it will lead to serious particle agglomeration, uneven fluidized bed oxidation, unbalanced micropore structure, and decreased first coulomb efficiency and cycle performance. If the proportion of the first particle size pickled precursor (small particle size) is too low, the surface area of the particles is insufficient, the depth of the oxidation reaction is limited, the specific capacity is reduced, and the rate performance is poor.
[0116] By comparing Example 1 with Examples 7-8, it can be seen that during the preparation process of the hard carbon negative electrode carbon material of the present invention, the gas flow rate of the fluidized bed oxidation treatment will affect its performance. When the gas flow rate of the fluidized bed oxidation treatment is controlled at 700mL / min~800mL / min, the performance of the hard carbon negative electrode material obtained is better. If the gas flow rate of the fluidized bed oxidation treatment is too large, the particle suspension is disordered and the oxidation reaction is uneven, which may lead to sintering of the material surface or destruction of the micropore structure, and a decrease in electrochemical performance. If the gas flow rate of the fluidized bed oxidation treatment is too small, the particle suspension is insufficient, the gas distribution is uneven, and the oxidation depth is limited, resulting in insufficient micropore formation, and the first coulomb efficiency and specific capacity are reduced.
[0117] By comparing Example 1 and Comparative Example 1, it can be seen that the present invention uses acid washing and deashing and fluidized bed pre-oxidation processes to greatly shorten the preparation cycle and reduce energy consumption. Compared with the traditional static oxidation method, the production efficiency is increased by more than 100%, and the consistency of the performance of the hard carbon material is improved.
[0118] By comparing Example 1 with Comparative Examples 2-3, it can be seen that the present invention improves the flowability of particles by compounding large and small particle size carbon precursors, reduces the risk of agglomeration of small particle size ultrafine sticky carbon particles, and significantly improves the heat transfer and mass transfer effects in the fluidized bed.
[0119] From the comparison between Example 1 and Comparative Example 4, it can be seen that the present invention adopts a fluidized bed oxidation process, which significantly improves the oxidation uniformity, oxidation efficiency and production controllability compared with tubular furnace oxidation. In the fluidized bed, the particles can fully contact with the oxidizing gas, avoiding local overoxidation or incomplete oxidation in tubular furnace oxidation, and ultimately improving the specific capacity, first coulomb efficiency and cycle performance of the hard carbon material.
[0120] By comparing and analyzing Example 3, Example 9 and Comparative Example 5, the difference in the oxidation process of the hard carbon negative electrode material preparation method of the present invention significantly affects the performance of the final hard carbon material. Compared with Example 3, the oxidation treatment of Example 9 is relatively simple, with only one pre-oxidation step, which may cause the final hard carbon material microstructure to be relatively loose, and the degree of carbonization during the carbonization process may not be as good as that of Example 3. The difference between Comparative Example 5 and Example 3 is reflected in the choice of oxidation treatment method. Comparative Example 5 uses tubular furnace oxidation instead of fluidized bed oxidation, and the other parameters are exactly the same as those of Example 3. Tubular furnace oxidation may cause the gas flow during the oxidation process to be less uniform than that of the fluidized bed, thereby affecting the oxidation degree and surface structure of the material, and further affecting the performance of the final hard carbon material. In summary, by comparing Example 3, Example 9 and Comparative Example 5, it can be seen that fluidized bed oxidation treatment is more conducive to the uniformity of the particle size distribution and carbonization effect of the hard carbon material than tubular furnace oxidation and single-stage oxidation treatment, thereby significantly improving the electrochemical properties of the hard carbon negative electrode material.
[0121] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a hard carbon negative electrode material, characterized in that: The preparation method comprises the following steps: (1) performing pickling and deashing treatment on a first particle size hard carbon precursor and a second particle size hard carbon precursor to obtain a first particle size pickled precursor and a second particle size pickled precursor, and mixing the first particle size pickled precursor and the second particle size pickled precursor to obtain a mixed pickled precursor; (2) subjecting the mixed acid-washed precursor to fluidized bed oxidation treatment and then screening to obtain an oxidized material with a first particle size and an oxidized material with a second particle size; (3) sintering the first particle size oxide material to obtain the hard carbon negative electrode material; Among them, the median particle size D50 of the first particle size pickling precursor is ≤30μm, the median particle size D50 of the second particle size pickling precursor is >30μm, the median particle size D50 of the first particle size oxide material is ≤30μm, and the median particle size D50 of the second particle size oxide material is >30μm.
2. The preparation method according to claim 1, characterized in that The median particle size of the first particle size hard carbon precursor is 2 μm≤D50≤30 μm, and the median particle size of the second particle size hard carbon precursor is 30 μm. <D50≤200μm; The median particle size of the first particle size pickling precursor is 2 μm ≤ D50 ≤ 30 μm, and the median particle size of the second particle size pickling precursor is 30 μm. <D50≤200μm; The median particle size of the first particle size oxide material is 2 μm ≤ D50 ≤ 30 μm, and the median particle size of the second particle size oxide material is 30 μm. <D50≤200μm。 3. The preparation method according to claim 1 or 2, characterized in that: In step (2), the second particle size oxide material is crushed and sieved to obtain an oxide material with a median particle size of 2μm≤D50≤30μm, which is then mixed with a new second particle size acid-washed precursor and the fluidized bed oxidation treatment and sieving steps of step (2) are repeated.
4. The preparation method according to any one of claims 1 to 3, characterized in that: Step (1) The first particle size hard carbon precursor and the second particle size hard carbon precursor are obtained by crushing, grinding, screening and drying the precursor carbon material; Preferably, the precursor carbon material includes any one or a combination of at least two of coal tar pitch, petroleum pitch, coal, biomass carbon material or heavy carbon material; Preferably, the drying temperature is 100°C to 110°C.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The pickling and deashing treatment in step (1) includes hydrochloric acid pickling and hydrofluoric acid pickling; Preferably, the mass concentration of hydrochloric acid used in the hydrochloric acid washing is 15% to 20%; Preferably, the solid-liquid mass volume ratio of the hydrochloric acid washing is 1:(5-15) g / mL; Preferably, stirring is performed during the hydrochloric acid washing process; Preferably, the stirring speed is 50 rpm to 150 rpm; Preferably, the stirring time is 10h to 15h; Preferably, the hydrochloric acid washing is followed by standing and water washing, silver nitrate is added to the water washing solution, and drying is performed after no white precipitate is generated; Preferably, the standing time is 1 h to 3 h; Preferably, the temperature of the drying treatment is 100°C to 110°C; Preferably, the drying time is 10h to 15h; Preferably, the mass concentration of the hydrofluoric acid used in the hydrofluoric acid washing is 35% to 45%; Preferably, the solid-liquid mass volume ratio of the hydrofluoric acid washing is 1:(5-10) g / mL; Preferably, stirring is performed during the hydrofluoric acid washing process; Preferably, the stirring speed is 50 rpm to 150 rpm; Preferably, the stirring time is 20h to 30h; Preferably, the hydrofluoric acid washing is followed by standing and water washing, calcium chloride is added to the water washing solution, and drying is performed after no white precipitate is generated; Preferably, the standing time is 2h to 4h; Preferably, the temperature of the drying treatment is 100°C to 110°C; Preferably, the drying treatment time is 10 hours to 15 hours.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In the mixed pickling precursor of step (2), the mass ratio of the first particle size pickling precursor to the second particle size pickling precursor is 1:(2-5); Preferably, the atmosphere of the fluidized bed oxidation treatment in step (2) comprises an oxygen-containing gas; Preferably, the gas flow rate of the fluidized bed oxidation treatment in step (2) is 700 mL / min to 800 mL / min; Preferably, the heating rate of the fluidized bed oxidation treatment in step (2) is 0.4°C / min to 1°C / min; Preferably, the temperature of the fluidized bed oxidation treatment in step (2) is 200° C. to 350° C.; Preferably, the fluidized bed oxidation treatment in step (2) includes a first stage fluidized bed oxidation treatment and a second stage fluidized bed oxidation treatment; Preferably, the temperature of the first stage fluidized bed oxidation treatment is 200°C to 300°C; Preferably, the first stage of fluidized bed oxidation treatment lasts for 2 hours to 6 hours; Preferably, the temperature of the second stage fluidized bed oxidation treatment is 300°C to 350°C; Preferably, the second stage of fluidized bed oxidation treatment lasts for 3 h to 5 h.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The atmosphere of the sintering treatment in step (3) comprises an inert gas; Preferably, the sintering temperature in step (3) is 1200° C. to 1500° C.; Preferably, the sintering time in step (3) is 3 h to 8 h; Preferably, the sintering treatment in step (3) is followed by an airflow classification and shaping treatment; Preferably, after the airflow classification and shaping treatment, the median particle size D50 of the hard carbon negative electrode material obtained is 2 μm to 10 μm.
8. A hard carbon negative electrode material, characterized in that: The hard carbon negative electrode material is prepared by the preparation method according to any one of claims 1 to 7.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises the hard carbon negative electrode material as claimed in claim 8.
10. A battery, characterized in that: The battery comprises the negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of hard carbon negative electrode material
CN107986254A
Preparation method and preparation device of coal pitch-based hard carbon negative electrode material
CN115188952A
Layered large-particle-size high-nickel single-crystal ternary positive electrode material and preparation method thereof
CN113644262A
Hard carbon material and preparation method and application thereof
CN116947012A